Privacy, confidentiality and the press. Issue 2 (8th December 2011) - ERHART, ITIR
Discussions on the right to privacy usually involve persons in the Lockean sense. However, psychological properties that make up the person can be lost due to neurodegenerative diseases, cerebral tumors or trauma. Depending on the severity of the disease or the trauma the patient may end up in PVS (persistent vegetative state) or a coma. In this article the privacy rights of these patients will be discussed. In light of two examples − the publication of photographs showing Bülent Ecevit and Barış Akarsu in a coma − it will be argued that the privacy rights secured by the Turkish Constitution are being violated by the Turkish Press.